Implementasi Pembelajaran Matematika Berbasis Open Ended Pada Mahasiswa Semester I Jurusan Akuntansi Fakultas Ekonomi Universitas Pamulang - Nelly Budiyarti (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to describe the implementation of Open Ended-based learning can improve Mathematics learning outcomes of the first semester S1 Accounting students at the University of Pamulang. Data collection is done by observation and tests. The results of the exam in the first cycle, 15 of 35 students or 43% of students passed the material